Risk factors for depression in postnatal first year, in eastern Turkey - Inandi, T; Elci, OC; Ozturk, A; Egri, M; Polat, A; Sahin, TK (Oxford Univ Press, 2002)
Background There are few studies reporting depression in the postnatal period in developing countries. In this study our objective was to evaluate women from eastern Turkey in the postnatal one-year period in order to analyse the risk factors for depression. Methods In this cross-sectional, multi-centre study, we selected a study sample from five eastern provinces. Among 2602 randomly selected women who gave birth within the last year, we included 2514 women in our analysis. The Edinburgh Postnatal Depression Scale was used for the evaluation of depression. Results The percentage of women with high depression scores was 27.2%. Excess risk of depression was associated with several factors including unemployment, low education, poverty, poor family relations, low marital age, lack of medical services, and mental health problems. Conclusions Depression in postnatal women is an important public health problem in the less developed eastern part of Turkey.
Keywords: maternal health; cross-sectional study; depression; postnatal; risk factors